Blood like magic - Sambury, Liselle (Sambury, Liselle. Blood like magic series, 2021)
After failing to come into her powers, sixteen-year-old Voya--a Black witch living in near-future Toronto--is forced to choose between losing her family's magic forever, a heritage steeped in centuries of blood and survival, or murdering her first love, a boy who is supposedly her genetic match.